Hierarchical Nanostructured Electrospun Membrane with Periosteum‐Mimic Microenvironment for Enhanced Bone Regeneration (Adv. Healthcare Mater. 21/2021). Issue 21 (3rd November 2021) - Liu, Laijun; Shang, Yuna; Li, Chaojing; Jiao, Yongjie; Qiu, Yanchen; Wang, Chengyi; Wu, Yuge; Zhang, Qiuyun; Wang, Fujun; Yang, Zhimou; Wang, Lu
Abstract : Bone Regeneration In article number 2101195, Chaojing Li, Fujun Wang, Zhimou Yang, Lu Wang, and co‐workers construct a hierarchical nanostructured electrospun membrane with a periosteum‐mimic microenvironment. As a periosteum functional substitute covering the surface of bone defects, it can continuously provide growth factors, recruit osteoblasts, causing subsequent extracellular matrix mineralization, and exhibits excellent vascularized bone regeneration effects in vivo.